The role of the forest fund in balancing the deficit of Forest Districts - Stebnicki, Michał (Journal of Public Governance, 2018)
The company Lasy Państwowe (State Forests) is financially autonomous and covers the costs of its activityfrom its own revenues (Chapter 8, Article 50, of the Act). It is not its objective to maximize profits but to perform economic, productive and non-productive natural and social functions. In order to ensure that such activities may be conducted throughout Poland, even in those forest districts where the costs are higher than the revenues generated, the forest fund has been established to offset financial deficits in loss-making forest districts. The forest fund is a financial instrument spent on tasks defined in the forest act, especially to offset deficits due to the costs of forest management, joint ventures of the company’s organizational units, creation of the infrastructure necessary to conduct forest management, as well as evaluating and estimating the forests and their resources. The rules of forest fund redistribution are not clearly specified, which is why each Regional Directorate of State Forests (RDSF) adopts different criteria relating to its redistribution. The aim of the paper is to define the role of the forest fund in balancing financial deficits in forest districts on the basis of data received from General Directorate of State Forests for the year 2014. The write-off in 2014 amounted to 14.5% of timber sales for individual RDSFs. Each RDSF differentiates the write-off and the subsidies from the forest fund for individual forest districts and inf luences liquidity and profitability of the forest districts it supervises.This paper was prepared on the basis of selected literature, analysis of materials received from the General Directorate of State Forests, own analyses and the experience gained in the course of professional work in the State Forests.